2022
DOI: 10.15562/bmj.v11i1.3225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum and vitreous TGF-β1 levels in proliferative diabetic retinopathy with and without panretinal photocoagulation laser therapy

Abstract: Introduction: A long-term diabetic retinopathy will cause an increase in several growth factors expression like Transforming Growth Factor β (TGF-β). This multipotent cytokine is involved in the process of endothelial cell proliferation. Therefore, this study aims to observe the relationship between TGF-β1 levels in serum and vitreous fluid of Proliferative Diabetic Retinopathy (PDR) patients given Pan Retinal Photocoagulation (PRP) laser therapy. Method: This was a cross-sectional study involving 14 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…TGF-β1 plays a role in wound healing through the proliferation and differentiation of fibroblasts, which results in the formation of myofibroblasts and the deposition of extracellular matrix, which induces fibrosis during the wound closure process. 14 MMP-8 (neutrophil collagenase) is a collagenase secreted by PMNs, macrophages, fibroblasts, epithelium, endothelial cells, and keratocytes. 15 Collagen is the most abundant structural protein in the human body and a key component of the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 plays a role in wound healing through the proliferation and differentiation of fibroblasts, which results in the formation of myofibroblasts and the deposition of extracellular matrix, which induces fibrosis during the wound closure process. 14 MMP-8 (neutrophil collagenase) is a collagenase secreted by PMNs, macrophages, fibroblasts, epithelium, endothelial cells, and keratocytes. 15 Collagen is the most abundant structural protein in the human body and a key component of the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…PPRP has been suggested in diabetic maculopathy [ 9 , 26 ] and macular edema related to retinal venous occlusion [ 27 , 28 ], and is the benchmark therapy for retinopathy of prematurity [ 29 ] and proliferative diabetic retinopathy (PDR) [ 12 ]. In PDR, PPRP appears to lower intraocular and plasma VEGF concentrations and to result in regression of ocular neovascularization [ 30 - 33 ]. In eyes with PDR, the aqueous level of VEGF significantly decreased as the extent of PPRP increased and had a significant correlation with total PPRP [ 34 ].…”
Section: Hypothesismentioning
confidence: 99%
“…Ichiyama et al [ 37 ] and Minaker et al [ 38 ] observed that aqueous VEGF levels were increased in active nAMD and that these levels markedly decreased following intravitreal anti-VEGF injections [ 39 ]. After PPRP, many proinflammatory cytokines are reduced [ 33 ]. The aqueous levels of several proinflammatory cytokines, including transforming growth factor β1 (TGF-β1), were markedly reduced in diabetic eyes after PPRP compared to those before PPRP [ 33 ].…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation